Role of Ethics in Promoting good Governance in the Society: A Study with Reference to Tasawwuf (Al-Qamar, 2021)
Society is a very complex machinery, and it is linked with human behavior. If it is positively merged with Theory and Practice, then it would help out humanity. Society and human behavior work together for the promotion of basic ethics and basic values in the community. Islam constitutes a comprehensive package of guidance for the Muslims in their individual as well as communal lives. Teachings about social interaction, social ethics, and social behavior are a very important part of Islam's guiding principles for good governance. This guidance is not from man or woman, from leaders or from scholars. This guidance is from Allah SWT through the Holy Prophet PBUH and Holy Quran, for the enhancement of the society. The ultimate goal of Islam is to create and then nourish a healthy society, all members of which are caring, loving and supportive towards each other.
Keywords: Ethics; good Governance; Society; Tasawwuf